Secret sharers : the intimate rivalries of modernism and psychoanalysis - Spitzer, Jennifer (Fordham University Press, 2023)
"Secret Sharers traces a genealogy of secret sharing between literary modernism and psychoanalysis, focusing on the productive entanglements and intense competitive rivalries that helped shape Anglo-American modernism as a field. As Jennifer Spitzer reveals, such rivalries played out in explicit criticism, inventive misreadings, and revisions of Freudian forms--from D. H. Lawrence's re-descriptions of the unconscious to Vladimir Nabokov's parodies of the psychoanalytic case study. While some modernists engaged directly with Freud and Freudian psychoanalysis with unmistakable rivalry and critique, others wrestled in more complex ways with Freud's legacy. The key protagonists of this study--D. H. Lawrence, Virginia Woolf, W. H. Auden, and Vladimir Nabokov--are noteworthy for the way they engaged with, popularized, and revised the terms of Freudian psychoanalysis, while also struggling with it as an encroaching discourse. Modernists read psychoanalysis, misread psychoanalysis, and sometimes refused to read it altogether, while expressing anxiety about being read by psychoanalysis--subjecting themselves and their art to psychoanalytic interpretations. As analysts, such as Freud, Ernest Jones, and Alfred Kuttner, turned to literature and art to illustrate psychoanalytic theories, modernists sought to counter such reductive narratives by envisioning competing formulations of the relationship between literature and psychic life. Modernists often expressed ambivalence about the probing, symptomatic style of psychoanalytic interpretation and responded with a re-doubling of arguments for aesthetic autonomy, formal self-consciousness, and amateurism. Secret Sharers reveals how modernists transformed the hermeneutic and diagnostic priorities of psychoanalysis into novel aesthetic strategies and distinctive modes of epistemological and critical engagement. In reassessing the historical and intellectual legacies of modernism, this book suggests that modernist responses to psychoanalytic criticism anticipate more recent critical debates about the value of 'symptomatic' reading and the 'hermeneutics of suspicion.'"--